Antipassive-like structures in the Polish language and their aspectual restrictions - Mroczyńska, Katarzyna (Papers in Linguistics, 2020)
The aim of this article is the presentation of the process of antipassivization, based on the material culled from the National Corpus of Polish (NKJP). The realization of antipassive-like structures in Polish is closely linked to the multifunctional, polysemous element się. In this work we discuss the classification of various antipassive-like structures occurring in Polish, based on Janic’s doctoral dissertation (Janic 2013), and illustrate it with numerous examples extracted from the NKJP. We also offer an explanation to certain aspectual restrictions in the occurrence of the antipassive-like structures, which may be seen in the corpus examples